CONCEPTUAL REVIEW OF AHARA VIDHI VISHESHAYATAN (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda defines health as balance of Dosha, Agni, Dhatu and Mala, as well as the physical, mental, emotional and spiritual wellbeing. This definition of health is in coherence with WHOs definition of Health as â€œA state of Physical, mental, Social and spiritual wellbeing and not merely an absence of disease. â€ Adequate nutrition is the basic need for the healthy life. Ayurveda places special emphasis on Ahara and believes that healthy nutrition nourishes the body, mind and soul. Nowadays, many lifestyle diseases are increasing day by day due to incorrect eating practices and cookery procedures. In Ayurveda classics emphasis has been laid regarding the right way to eating food. Food consumed in the right manner serves as nectar to rejuvenate the body and maintaining the health. Ayurveda offers some basic dietary guidelines that include choosing appropriate food, combinations of food, cooking methods, quality & quantity of food, nature of consumer, geographical and environmental conditions etc. Ayurveda classics describe all these aspects in a very systematic and scientific manner which is called as Ahara Vidhi Visheshayatane. These are 8 major aspects of food convention that includes compatibility of food articles which are determinant factors for the maintenance of Health. It gives a fair idea about what? When? Why? How? and Which? Food material should be consumed for promotion of positive health. A thorough understanding of these fundamentals will help in reducing the digestive distress due to lifestyle disorder and achieving the noble goal of maintaining Health.